THE EFFECT OF CURCUMA XANTHORRHIZA ETHANOL EXTRACT ON THE VIABILITY OF STREPTOCOCCUS MUTANS AND AGGREGATIBACTER ACTINOMYCETEMCOMITANS (DENTAL BIOFILM RESEARCH: IN VITRO STUDY) - Diana, Royan; Joenoes, Hedijanti; Djais, Ariadna A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to compare the effect of Curcuma xanthrorrhiza ethanol extract to the viability of Streptococcus mutans andÂ AggregatibacterÂ Â actinomycetemcomitans using single- and dual-species biofilm at different phases of formation. Methods: Biofilm models were incubated for 4, 12, and 24 hrs, then exposed to the extract at a concentration of 0.525%. Results: The viability of the single-species S. mutans biofilm was low (p<0.05), and no significant difference (p>0.05) was found between singlespeciesA.Â actinomycetemcomitansÂ and dual-species biofilm. Conclusions: Curcuma xanthorrhiza ethanol extract is more effective for decreasing the viability of single-species S. mutans biofilm.